Peran Corporate Governance sebagai Variabel Moderasi dalam Hubungan antara Struktur Modal dan Profibilitas terhadap Nilai Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia - Santiasari Santiasari; Chairul Adhim; Desi Rubiyanti (Jurnal Manajemen dan Ekonomi Kreatif, 2026)
This study aims to analyze the effect of capital structure and profitability on firm value with corporate governance as a moderating variable in manufacturing companies listed on the Indonesia Stock Exchange during the 2022–2024 period. Using a quantitative approach, the study applies Moderated Regression Analysis (MRA) to examine direct and moderating relationships among the variables. The sample consists of 60 manufacturing companies, producing 180 firm-year observations. The results show that capital structure has no significant effect on firm value, indicating that debt composition is not the main determinant of market valuation in the observed companies. Conversely, profitability has a positive and significant effect on firm value, demonstrating that stronger earnings performance increases investor confidence and company valuation. Corporate governance is unable to moderate the relationship between capital structure and profitability on firm value. Simultaneously, all research variables significantly affect firm value. These findings confirm that profitability is the primary factor supporting firm value, while corporate governance requires stronger implementation mechanisms.